administrative resolution no 436/2015 regarding amending certain provisions of the resolution of the heads of the Egyptian tax authority and the customs authority 293/2011 Concerning Banderoles and sticking procedures Thereof = قرار إداري رقم 436 لسنة 2015 بشأن تعديل بعض أحكام قرار رئيسي مصلحتي الضرائب والجمارك المصرية رقم 293 لسنة 2011 الخاص بالعلامات المميزة وإجراءات لصقها / Minister Prime - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of Finance the Egyptian Customs Authority Administrative Resolution no. 436 of the year 2015 regarding amending certain provisions of the resolution of the heads of the Egyptian Tax Authority and the Customs Authority no. 293 of the year 2011 concerning banderoles and sticking procedures thereof وزارة الماليى مصلحة الجمارك المصرية قرار إدارى رقم 436 لسنة 2015 بشأن تعديل بعض أحكام قرر رئيسى مصلحتى الضرائي والجمارك المصرية رقم 293 لسنة 2011 الخاص بالعلامات المميزة وإجراءات لصقها